S1P-dependent interorgan trafficking of group 2 innate lymphoid cells supports host defense - Huang, Yuefeng; Mao, Kairui; Chen, Xi; Sun, Ming-An; Kawabe, Takeshi; Li, Weizhe; Usher, Nicholas; Zhu, Jinfang; Urban, Jr, Joseph F; Paul, William E; Germain, Ronald N (Science (American Association for the Advancement of Science), 2018)
Innate lymphoid cells (ILCs) are innate counterparts of adaptive T lymphocytes, contributing to host defense, tissue repair, metabolic homeostasis, and inflammatory diseases. ILCs have been considered to be tissue-resident cells, but whether ILCs move between tissue sites during infection has been unclear. We show here that interleukin-25- or helminth-induced inflammatory ILC2s are circulating cells that arise from resting ILC2s residing in intestinal lamina propria. They migrate to diverse tissues based on sphingosine 1-phosphate (S1P)-mediated chemotaxis that promotes lymphatic entry, blood circulation, and accumulation in peripheral sites, including the lung, where they contribute to anti-helminth defense and tissue repair. This ILC2 expansion and migration is a behavioral parallel to the antigen-driven proliferation and migration of adaptive lymphocytes to effector sites and indicates that ILCs complement adaptive immunity by providing both local and distant tissue protection during infection.